Examining the Interrelationships Among Internal Control Systems, Love of Money, Morality, and the Propensity for Corruption (E-Jurnal Akuntansi, 2026)
This study seeks to investigate the impact of the internal control system, love of money, and morality on the propensity for corrupt behavior within the Regional Financial and Asset Management Agency (BPKAD) of Bali Province. The research includes a population of 153 respondents, encompassing all employees of the BPKAD. Data were analyzed using multiple linear regression techniques to identify the relationships between the variables. The results indicate that both the internal control system and morality negatively influence the likelihood of engaging in corrupt practices, while the love of money demonstrates a positive association with corrupt behavior.
Keywords: Internal Control System; Love of Money; Morality and Corruption Tendencies